WHEAT YIELD RESPONSE TO PHYSIOLOGICAL LIMITATIONS UNDER WATER STRESS CONDITION - A. A. Khakwani; M. D. Dennett; M. Munir; M. S. Baloch (Journal of Animal and Plant Sciences, 2012)
The objective of this research was to determine the response of wheat varieties (Damani, Hashim-8, Gomal-8, DN-73, Zam-04 and Dera-98) under irrigated (100% field capacity) and drought stress (35% field capacity). Analysis of variance revealed significant effect of water stress on chlorophyll fluorescence, chlorophyll content, stomatal conductance, stomatal dimension, stomatal density, leaf fresh weight, leaf dry weight, leaf area, specific leaf area (SLA), relative water content (RWC) and grain yield per plant. Although all six varieties behaved independently but significantly for mentioned physiological and yield traits, however Hashim-8, Zam-04 and Damani showed best candidates for rainfed regions, recording minimum percent reduction when grown under 35% field capacity (65% drought) in all above-mentioned traits. The same rainfed varieties also retained higher level of stomatal conductance and RWC under water stress condition and minimum percent reduction in stomatal dimension and stomatal density, which reflect their adoptability under drought condition.
Keywords: Wheat; Triticum aestivum; Stomata; Chlorophyll content; Drought; Water stress; Yield